Hyperuricemia and clustering of cardiovascular risk factors in the Chinese adult population - Jie Wu (Nature Portfolio, 2017)
Abstract Hyperuricemia is common in China and the relevance of hyperuricemia and cardiovascular disease (CVD) risk has been highlighted, but to date there has been rarely nation-wide study in China. Here, we aim to estimate the current prevalence of hyperuricemia and evaluate the associations between hyperuricemia and cardiovascular risk factors (CRFs) clustering in a large sample of China adults including a plurality of ethnic minorities. Generally, a nationally representative sample of 22983 adults aged ≥18 years was recruited from 2007 to 2011. Questionnaire data and information on anthropometric characteristics, and laboratory measurements were collected. We define hyperuricemia as SUA ≥416 mmol/L for men and SUA ≥357 mmol/L for women. We found that the prevalence of hyperuricemia was 13.0% (18.5% in men and 8.0% in women). To our estimation, hyperuricemic subjects had higher prevalence rates of CRFs clustering than non-hyperuricemic subjects. Furthermore, there was a dose-response association between the number of CVD risk factors clustering and hyperuricemia. Our study revealed a high prevalence of hyperuricemia and CVD risk factors clustering among Chinese adults, and hyperuricemia was significantly associated with coexistence of more CVD risk factors. Therefore, guidance and effective lifestyle intervention are required to prevent hyperuricemia and CVD risk factors in China.